Case report: Progressive multifocal leukoencephalopathy co-occurring with neurosarcoidosis: early brain biopsy and appropriate therapy for PML resulted in a favorable prognosis - Wang, Qiannan; Tsuboguchi, Shintaro; Okamoto, Kouichirou; Tada, Mari; Kakita, Akiyoshi; Nakamichi, Kazuo; Oishi, Makoto; Kanazawa, Masato; Onodera, Osamu (Frontiers in Immunology, 2024)
Progressive multifocal leukoencephalopathy (PML) is a rare central nervous system disease caused by JC virus (JCV) infection. Human immunodeficiency virus (HIV) infection is the greatest risk factor for PML. Other immunological diseases, including systemic sarcoidosis, have also been reported as risk factors for PML. Herein, we report a case of PML co-occurring with neurosarcoidosis. Early diagnosis using brain biopsy and appropriate therapeutic interventions achieved favorable outcomes. PML in patients with active intracranial neurosarcoidosis is extremely rare. We believe that it is important to perform brain biopsy at an early stage to allow diagnosis, even for central nervous system involvement with a progressive parenchymal lesion in patients with sarcoidosis, if PML is possible.